Nutritional status, hemoglobin, and albumin levels in predicting platinum resistance in ovarian cancer at Dr. Saiful Anwar Hospital, Malang, Indonesia - Tatit Nurseta; Ayu Rizky Widowati (Majalah Obstetri dan Ginekologi)
HIGHLIGHTS